INCREASED USE OF E-MONEY DURING THE COVID 19 PANDEMIC - Walid Rudianti; Siti Maesaroh (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2023)
The implementation of information technology has been widely used in daily activities in society, which is indicated by the presence of various information technology facilities developed for the community. The emergence of smartphones is solid evidence of the existence of sophisticated technology as a form of creativity and innovation created by humans in this modern era. The Covid-19 pandemic that started in early 2019 also played a role in the increased use of e-money. Based on the results of a pre-survey of students at three tertiary institutions in Banjarnegara, namely STIE Tamansiswa Banjarnegara, Banjarnegara Polytechnic, and STIMIK Tunas Bangsa, it was found that only 7% had not used e-money. So, it can be concluded that most Banjarnegara students already use e-money to make payments. This study aims to influence the factors that influence interest in using e-money. This research was conducted in Banjarnegara Regency, and the research sample was 236 respondents. Data collection techniques in this study were carried out by distributing questionnaires. The analysis technique used is the classical assumption test, and the hypothesis test used is multiple linear regression. The results of this study state that partially, the variables of discounts, ease of use, and transparency have a significant effect on the intention to use e-money. The results simultaneously state that the variables of discounts, ease of use, and transparency significantly affect the choice to use e-money, with an R Square value of 78.1%.